A Sociolinguistic Consideration of Intermediation in Greeting Discourse among the Yo?ru?ba of South West Nigeria - Bolanle Tajudeen Opoola; Jelili Adewale Adeoye (Universitas Sanata Dharma, 2019)
Existing studies on Yoru?ba? greeting forms dwell on the appropriateness of their use, with respect to time of the year, event, condition, occupation, vocation, context, politeness and content. The studies portray greetings as discourse between two people or parties who are capable of exchanging pleasantries. None of the existing works has discussed intermediation in greeting discourse among the Yoru?ba? people such that greetings that are directed to the second person(s) such as toddlers, extremely sick persons, kings and the bereaved are answered on their behalf by a third party. This paper examines intermediation and the rationale in greeting discourse among the Yoru?ba? people. The data for this study were drawn from participant observation, Yoru?ba? literature texts, and Yoru?ba? home movies. The Mutual Contextual Beliefs Theory of Pragmatics as proposed by Bach and Harnish (1979) was adopted for the data analysis. The study established, among other things, that greetings are sacrosanct in Yoru?ba? culture and the answer/reply is obligatory, irrespective of the state, status, circumstance and condition of the person(s) being greeted. It is also shown that intermediation in greeting discourse could be for politeness, incapacitation, authority and educating the young ones.